2012
DOI: 10.1007/s00216-012-6021-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the spin-trapping reaction of a free radical derived from AAPH: further development of the ORAC-ESR assay

Abstract: The characteristics of the spin-trapping reaction in the oxygen radical absorbance capacity (ORAC)-electron spin resonance (ESR) assay were examined, focusing on the kind of spin traps. 2,2-Azobis(2-amidinopropane) dihydrochloride (AAPH) was used as a free radical initiator. The spin adducts of the AAPH-derived free radical were assigned as those of the alkoxyl radical, RO· (R=H(2)N(HN)C-C(CH(3))(2)). Among the spin traps tested, 5,5-dimethyl-1-pyrroline N-oxide (DMPO), 5,5-dimethyl-4-phenyl-1-pyrroline N-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…The c 50 values of phenolic compounds with catechol group were CA [ CAT * EP [ RTN, which suggested that the functional group directly combined with the catechol group retarded strongly the elimination of alkoxyl radical by catechol group and the order of the retardation was -C=CH-CH-COOH \ chroman * -CH 2 CH-NH 2 -COOH. As extra free radical, such as hydroxyl radical which was observed in the optical-irradiation system [5], did not produce in the present system, valid c 50 values for phenolic compounds could be obtained. The ratio of maximum c 50 value (CA) to minimum (MAN) was 5500, the ratio of maximum ID 50 for superoxide radical (TRP) to minimum (CAT) was 9200, and the ratio of maximum ID 50 for hydroxyl radical (MAN) to minimum (TRX) was 150.…”
Section: Antioxidant Ability Of Selected Phenolic Compounds and Biosumentioning
confidence: 72%
See 4 more Smart Citations
“…The c 50 values of phenolic compounds with catechol group were CA [ CAT * EP [ RTN, which suggested that the functional group directly combined with the catechol group retarded strongly the elimination of alkoxyl radical by catechol group and the order of the retardation was -C=CH-CH-COOH \ chroman * -CH 2 CH-NH 2 -COOH. As extra free radical, such as hydroxyl radical which was observed in the optical-irradiation system [5], did not produce in the present system, valid c 50 values for phenolic compounds could be obtained. The ratio of maximum c 50 value (CA) to minimum (MAN) was 5500, the ratio of maximum ID 50 for superoxide radical (TRP) to minimum (CAT) was 9200, and the ratio of maximum ID 50 for hydroxyl radical (MAN) to minimum (TRX) was 150.…”
Section: Antioxidant Ability Of Selected Phenolic Compounds and Biosumentioning
confidence: 72%
“…The rate constant of alkoxyl radical formation (Eqs. 3 and 4) is about 10 5 M -1 s -1 [8], and the spin adduct, DMPO/OR should be fairly stable [5]. The spin adduct, DMPO/OR, was only observed in the present system.…”
Section: Evaluation Of Antioxidant Abilitymentioning
confidence: 91%
See 3 more Smart Citations